FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN DALAM PENGGUNAAN LAYANAN KESEHATAN PADA WILAYAH KERJA PUSKESMAS TAWIRI - Nusawakan, Arwyn W; Tesabela Messakh, Sanfia; Jambormias, Sevnat (MEDIA ILMU KESEHATAN, 2017)
Background: Health is one of the important aspects in human life that will be maintained. The effort to maintain includes the right of decision-making to use health services provided in the community. Data on access to health services and facilities shows low number of visits to these facilities and it arises the question of the reason behind the low number of access. Objective: The purpose is to identify factors affecting the decision-making in the use of health services by the community of Hative Besar Village, Ambon-Maluku. Method: The approach used in this study is qualitative descriptive. Data is collected through semi-structured, in-depth interview. 8 natives of Hative Besar Village, Ambon-Maluku are involved as research participants. Result: Decision making in the use of health services by the community influenced by health-illness perception, professional services and the experience of using health care services are major factors that influence the Hative Besar village perception and later cause the emergence of factors decision in family and the cost. Conclusion: Factors that influence the decision-making by the community of Hative Besar Village in the use of health care facilities are health-illness perception, the experience of using health care services, professional services, decision in family and the cost. Keywords: Health, decision, community, health care